Respon Beberapa Varietas Kedelai (Glycine max (L.) Merril) dengan Pengaturan Jarak Tanam - Zega, Setiawan; Wardati, Wardati; Zuhry, Elza (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2020)
The research aims to determine the response of several varieties of soy (Glycine max (L.) Merril) with the arrangement of distance planting for growth and production and gaining the best varieties and distances. This research has been conducted in the Faculty of Agriculture Plantation University of Riau, campus Bina Widya km 12.5 village Simpang Baru, Tampan district, Pekanbaru city. This research has been conducted from November 2017 to February 2018. Research is conducted experimentally using a group of random plans (RAK), compiled factorial with 2 factors and 3 repeats. The first factor is a variety consisting of V1 (Argomuolyo), V2 (Anjasmoro), V3 (Wilis). The second factor is the arrangement of distances consisting of J1 (40 cm x 15 cm), J2 (40 cm x 20 cm), J3 (40 cm x 25 cm). There are 9 combinations of treatments and each treatment is repeated 3 times, resulting in 27 units of tests. The observed parameters are high crop, root header ratio, dry weight of the plant, flowering plant age, number of main branches, Harvest age, number of righteous pods per plant, number of seeds per plant, weighing 100 seeds, weight of seeds per m2. Data obtained from subsequent observations is analyzed statistically using various fingerprints. The print results were continued with Duncan's multi-distance test at 5%. Results showed that the use of varieties Argomulyo with planting distance 40 cm x 15 cm can increase the growth and production of soy compared with other treatments.Keywords : soybean, varieties, planting space, growth, production